Assessing the variation in manganese use efficiency traits in Scottish barley landrace Bere (Hordeum vulgare L.) - Cope, Jonathan E (Ann Bot, 2020)
BACKGROUND AND AIMS: Manganese (Mn) deficiency in barley is a global problem. It is difficult to detect in the early stages of symptom development and is commonly pre-emptively corrected by Mn foliar sprays that can be costly. Landraces adapted to marginal lands around the world represent a genetic resource for potential sustainability traits including mineral use efficiency. This research aims to confirm novel Mn use efficiency traits from the Scottish landrace Bere and use an association mapping approach to identify genetic loci associated with the trait. METHODS: A hydroponic system was developed to identify and characterize the Mn deficiency tolerance traits in a collection of landraces, including a large number of Scottish Bere barleys, a group of six-rowed heritage landraces grown in the highlands and islands of Scotland. Measuring chlorophyll fluorescence, the effect of Mn deficiency was identified in the early stages of development. Genotypic data, generated using the 50k Illumina iSelect genotyping array, were coupled with the Mn phenotypic data to create a genome-wide association study (GWAS) identifying candidate loci associated with Mn use efficiency. KEY RESULTS: The Bere lines generally had good Mn use efficiency traits. Individual Bere lines showed large efficiencies, with some Bere lines recording almost double chlorophyll fluorescence readings in limited Mn conditions compared with the elite cultivar Scholar. The Mn-efficient Bere lines had increased accumulation of Mn in their shoot biomass compared with elite cultivars, which was highly correlated to the chlorophyll fluorescence. Several candidate genes were identified as being associated with Mn use efficiency in the GWAS. CONCLUSIONS: Several genomic regions for Mn use efficiency traits originating from the Bere lines were identified. Further examination and validation of these regions should be undertaken to identify candidate genes for future breeding for marginal lands.